Synchronization of turbo coded modulation systems at low SNR - Lijun Lu; Wilson, S.G. (1998 IEEE International Conference on Communications, 1998)
This paper examines the synchronization of turbo coded modulation systems at low SNR where these systems are designed to operate. Maximum likelihood estimation theory is used to derive a causal, discrete-time synchronization structure for estimating the carrier phase and symbol timing of a general QAM signal, using a decision-directed structure which is known to be superior at low SNR. Simulation shows that efficient joint carrier phase and symbol timing estimates can be acquired using our synchronizer for turbo codes. Bit error performance for selected loop bandwidths is presented.